2013
DOI: 10.1103/physreve.87.043014
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic interaction of spherical particles under Quincke rotation

Abstract: Weakly conducting dielectric particles suspended in a dielectric liquid of higher conductivity can undergo a transition to spontaneous sustained rotation when placed in a sufficiently strong dc electric field. This phenomenon of Quincke rotation has interesting implications for the rheology of these suspensions, whose effective viscosity can be controlled and reduced by application of an external field. While previous models based on the rotation of isolated particles have provided accurate estimates for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 47 publications
5
67
0
2
Order By: Relevance
“…Pickering drops) [13,14] suspended in a bulk liquid, and we find that two such deformable rotors can spontaneously self-organize into a counter-rotating pair, and be propelled as the result of their mutual interacting hydrodynamic flow fields. This observation is in agreement with recent models for two-rotor systems of low-Reynolds number swimmers [15] [16], and numerical simulations of interacting Quincke rotating particles [17].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Pickering drops) [13,14] suspended in a bulk liquid, and we find that two such deformable rotors can spontaneously self-organize into a counter-rotating pair, and be propelled as the result of their mutual interacting hydrodynamic flow fields. This observation is in agreement with recent models for two-rotor systems of low-Reynolds number swimmers [15] [16], and numerical simulations of interacting Quincke rotating particles [17].…”
Section: Introductionsupporting
confidence: 91%
“…Quincke rotation of a particle suspended in a liquid is driven by the electric forces acting on the free charges that build up at the surface of a particle [4,5,6,17]. The instability only occurs if the Maxwell-Wagner electric charge relaxation time of the particle is longer than that of the surrounding fluid, in which case the effective dipole moment of the particle is anti-parallel to the applied electric field.…”
Section: Quincke Rotation: Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be shown that the dynamics of P σ is not coupled to the other multipoles, see e.g. [33], and obeys…”
Section: A a Roller In Heterogeneous Fieldsmentioning
confidence: 99%